PENYIDIKAN TINDAK PIDANA PEMALSUAN SURAT AKTA JUAL BELI TANAH DI WILAYAH POLISI RESOR KOTA PEKANBARU - Yohanes Frans; Erdianto '; Rahmad Hendra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
The criminal act of forgery stipulated in Chapter XII Book II Criminal Code on forgery, the book lists that are included falsification only form of writings alone, including forgery under Article 263 paragraph (1) of the Criminal Code, which reads: "Whoever makes the letter false or forged which can cause something right, commitment or debt relief, or which is applied as proof of the thing with intent to use or get someone else to wear the letter as if it was true and not doctored, threatened that if the use can cause losses, because of forgery, with a maximum imprisonment of six years.As for the purpose of this study include: First, to know the process of investigation in uncovering the crime of counterfeiting Letter Deed of Sale and Purchase of Land in the area of police resort city of Pekanbaru, second, to determine the obstacles investigators in addressing the Crime of forgery Deed of Sale and Purchase of Land in the region police resort city of Pekanbaru, Third, to determine the investigators efforts in addressing the Crime of forgery Deed of Sale and Purchase of Land in the resort city of Pekanbaru police.This research is a sociological research that want to see the correlation between law and society. This research was conducted in the city of Pekanbaru Police Resort, both the population and the sample was also conducted in the city of Pekanbaru Police Resort. In this study the data source used, primary data and secondary data, the data collection techniques in this study with interviews, and a review of the literature.From the research problem there are three main things that can be inferred First, the implementation of the investigation in uncovering the crime of falsification of the Deed of Sale and Purchase of Land in the area of police resort city of Pekanbaru, Second, barriers to investigators in overcoming the crime of counterfeiting Letter Deed of Sale and Purchase of Land in the area of police Resort City Pekanbaru, Third, investigators efforts in addressing the crime of forgery of the Deed of Sale and Purchase of Land in the resort city of Pekanbaru Police. Suggestions Author, First, activity implementation investigation Police Pekanbaru City should be improved so that the investigation can be carried out quickly done, Second, should the City Police Pekanbaru should cooperate with relevant parties such as the National Land Agency of Pekanbaru and the investigator should be more assertive in dealing with criminal offenses of forgery Deed of Sale and Purchase of land, Third, should the type of letter should be reduced, because of the many types of land documents at this time would make it easier to manipulate the perpetrators of the land documents.Keywords: Crime and Forgery – Investigation